(NtONKAQ STRUKTURA REGULQRNYH GEOMAGNITNYH WARIACIJ NA SREDNIH I NIZKIH [IROTAH (B/s - (NpOGREBNOJ(B, (NwALENTIN nIKOLAEWI^s ((NfRUNZE (B:s (NiLIM(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 136-148 (149 (NNAZW(B.)s
(Nan kIRGssr(B, (NiN(B-(NT SEJSMOLOGIIs
Keywords: (NmAGNITNOE POLE zEMLIs